2011
DOI: 10.1111/j.1582-4934.2011.01286.x
|View full text |Cite
|
Sign up to set email alerts
|

Migration of bone marrow‐derived cells and improved perfusion after treatment with erythropoietin in a murine model of myocardial infarction

Abstract: Erythropoietin (EPO) was shown to have protective effects after myocardial infarction (MI) by neovascularization and antiapoptotic mechanisms. Beside direct receptor-dependent mechanisms, mobilization and homing of bone marrow-derived cells (BMCs) may play a pivotal role in this regard. In this study, we intended to track different subpopulations of BMCs and to assess serially myocardial perfusion changes in EPO-treated mice after MI. To allow tracking of BMCs, we used a chimeric mouse model. Therefore, mice (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…(iv) Functionally, G-CSF significantly improved survival and preserved LV function after TAC procedure. In the last years, several studies focused on the endogenous repair mechanisms after mobilization of BMCs by cytokines, like G-CSF [9,11,18], parathyroid hormone [10,13,19,20] or erythropoietin [21,22] in ischaemic diseases like MI. It could be clearly demonstrated that the interaction of SDF-1 with its ligand CXCR4 plays a major role in the migration of BMCs into ischaemic cardiac tissue, which was associated with attenuated remodelling and improved function [12,23].…”
Section: Discussionmentioning
confidence: 99%
“…(iv) Functionally, G-CSF significantly improved survival and preserved LV function after TAC procedure. In the last years, several studies focused on the endogenous repair mechanisms after mobilization of BMCs by cytokines, like G-CSF [9,11,18], parathyroid hormone [10,13,19,20] or erythropoietin [21,22] in ischaemic diseases like MI. It could be clearly demonstrated that the interaction of SDF-1 with its ligand CXCR4 plays a major role in the migration of BMCs into ischaemic cardiac tissue, which was associated with attenuated remodelling and improved function [12,23].…”
Section: Discussionmentioning
confidence: 99%
“…EPO is a growth factor exerting effects at diverse targets in addition to its well-known classical action to stimulate erythrocyte production. We have earlier found EPO to exert cardio-protective effects due to intrinsic anti-apoptotic properties and also due to mobilisation of bone marrow-derived stem cells [ 13 , 14 , 29 , 30 ]. The first clinical trial of EPO in patients with chronic heart failure gave promising findings of increased exercise capacity and cardiac function [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative results were compared with reference standard LV-function measurements obtained with 1.5 T clinical MRI. We then proceeded to test gated FDG-PET for longitudinal monitoring in mice with CVB3-induced DCM after erythropoietin (EPO) treatment, based upon previous reports of its cardioprotective properties in preclinical models of myocardial infarction [ 13 , 14 ] as well as in rats with autoimmune-induced myocarditis [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Growth factors, such as erythropoietin (EPO), can form a vital component for both neuronal and vascular cells and rely upon mTOR pathway signaling. EPO controls neuronal, inflammatory cell, and endothelial cell survival (Brunner et al , 2012; Caprara and Grimm, 2012; Chalhoub et al , 2012; Chong et al , 2002, 2003a; Eipel et al , 2012; Maiese et al , 2008b; Maiese et al , 2008d; Okaji et al , 2012; Shang et al , 2012; Talving et al , 2012). EPO governs mTOR signaling for microglia survival during oxidative stress (Shang et al , 2011) and for osteoblastogenesis and osteoclastogenesis (Kim et al , 2012).…”
Section: Stem Cell Proliferation and Differentiation With Mtormentioning
confidence: 99%